Influence of phenyl-urea and adenine-type cytokinins on direct adventitious shoot regeneration of cabbage (Brassica oleracea subsp. capitata) “KY Cross” - Ravanfar, Seyed Ali; Salim, Shahida; Abdul Aziz, Maheran; Abdullah, Siti Nor Akmar; Abdul Rashid, Azmi (Japanese Society for Plant Cell and Molecular Biology, 2014)
In this study, the effects of phenyl-urea (Thidiazuron) and adenine (6-benzylaminopurine) and 6- y,y,dimethylally-amino purine type cytokinins alone or in combination with indole-3-butyric acid on shoot regeneration from hypocotyl and cotyledonary explants of Brassica oleracea ssp. capitata “KY Cross” were investigated. For hypocotyl explants, medium containing 2.27 μM Thidiazuron showed the highest mean number (18.15) of separable shoots per explant with 80% shoot formation. In the case of cotyledonary explants, the highest mean number of shoots (3.03) was obtained on medium containing 12.30 μM 6-y,y,dimethylally-amino purine with a percentage of 56.67% shoot formation. Plantlets were successfully acclimatized with 70% survival in potting medium consisting of coconut husk+vermicompost (7 : 1 v/v). The regeneration system developed herewith will be a valuable tool for genetic improvement of cabbage “KY Cross”.